Lychee-like ZnO/ZnFe2O4 core-shell hollow microsphere for improving acetone gas sensing performance. Issue 5 (1st April 2020) - Hu, Yu; Wang, Hong; Liu, Di; Lin, Guo; Wan, Jiawei; Jiang, Huan; Lai, Xiaoyong; Hao, Shuaijun; Liu, Xiaohua
Abstract: Uniformly lychee-like ZnO/ZnFe2 O4 core-shell hollow microspheres with average size of 2.5 μm were successfully synthesized via one-step solvothermal self-assembly route. The core-shell hollow microspheres possessed mesoporous structure with a pore size of about 8.8 nm and the large specific surface area of approximately 54.0 m 2 /g. The effect of the Zn 2+ concentration on the structure, morphology and gas-sensing property of the as-prepared samples were investigated by a series of testing techniques. The gas-sensing results demonstrated that the sensors based on core-shell ZnO/ZnFe2 O4 hollow microspheres showed superior gas-sensing response, rapid response-recovery to low-ppm acetone. These excellent properties might be mainly owing to the unique core-shell structure, the large specific surface area, high concentration of oxygen vacancies and the synergetic effect between ZnO and ZnFe2 O4 . Hence, this material can be utilized as promising gas-sensing materials in the acetone detection.